2010
DOI: 10.1590/s1984-29612010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Lutzomyia longipalpis Lutz & Neiva, 1912 in an area of intense transmission of visceral leishmaniasis in Rio Grande do Norte, Northeast Brazil

Abstract: Urban increase of visceral leishmaniasis (VL) in Brazil is associated with the adaptation of its vector, Lutzomyia longipalpis, to environments modified by humans. The present study reports the results of an entomological monitoring of L. longipalpis and the effect of environmental variables on its population density. Sandflies were captured in the municipality of Mossoró, State of Rio Grande do Norte, Northeastern Brazil, from January 2005 to December 2006. Two CDC light traps were placed monthly for four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
8
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
5
8
0
4
Order By: Relevance
“…These conditions are known to favor the presence of L. longipalpis (MICHALSKY et al, 2009), the predominant phlebotomine species in the city. Similar results were found in a previous monitoring survey by the same research group (AMÓRA et al, 2010).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These conditions are known to favor the presence of L. longipalpis (MICHALSKY et al, 2009), the predominant phlebotomine species in the city. Similar results were found in a previous monitoring survey by the same research group (AMÓRA et al, 2010).…”
Section: Resultssupporting
confidence: 91%
“…The significantly higher proportion of sand flies in the peridomicile was also reported in other municipalities in Rio Grande do Norte (XIMENES et al, 2000(XIMENES et al, , 2007, in the city of Mossoró, as mentioned earlier (AMÓRA et al, 2010), and in Montes Claros, state of Minas Gerais, southeastern Brazil, where sand flies were captured near domestic animals (MONTEIRO et al, 2005). These findings can be explained by the devastation of large wild areas for economic exploration, bringing the disease to the periphery of urban centers.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, in northeastern Brazil, where temperatures vary little throughout the year, the greater abundance of the vector occurs during the rainy season, which ranges from June to August 10,11,31 . In other studies performed in the cities of Porteirinha 23 and Montes Claros 25 , both of which are located in Minas Gerais in southeastern Brazil, the rainfall and the temperature were considered to be predictors of vector abundance.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the relationship between environmental variables and the density of vectors 7,8 ; in particular, areas that fl ood during the rainy season due to their proximity to rivers are more vulnerable to VL because they have a higher insect density, particularly around homes 9 .…”
Section: Introductionmentioning
confidence: 99%